The material-structure duality of rock mass: Insight from numerical modeling. (August 2021) - Li, Gen; Cheng, Xiaofeng; Hu, Lihua; Tang, Chunan
Abstract: The roots of rock engineering disaster lie not only in cross-scale deterioration and failure of rock material, but also in large deformation and instability of rock discontinuities and structural bodies. The material-structure duality of rock mass influences the mechanical behavior of rock mass, resulting in continuous-discontinuous characteristics and singularity phenomena. Nevertheless, the cognition of the dominant transformation and cooperative effect between these complex mechanisms is still vague, and there is a lack of a numerical scheme considering both material and structral effects of rock. In this study, we constructed a unified numerical scheme (Rock failure and instability analysis, RFIA) that considers both material failure and structural instability of rock mass. By establishing the statistical meso-damage constitutive model, the damage and failure of rock materials were reflected, and by developing the finite deformation numerical formation considering current state response, the large deformation and instability of rock structural body were described. The proposed numerical scheme realized the synchronous simulation of both material failure induced instability, and structural instability induced failure of rock mass. The size effect on rock under uniaxial compression and the local collapse mechanism of the surrounding rock in deep slabbing tunnel were investigated by RFIA. Meanwhile, Rock failure analysis (RFA) that only considers rock material failure and Rock instability analysis (RIA) that only considers structural instability were performed in the simulations. The results show that there are dominant and competitive mechanisms between material failure and structural instability during failure and instability process of rock. For the rock structral body with dominant geometric features, its instability plays a decisive role in inducing catastrophe. The cooperative effect of material-structure is an important mechanism, which may result in large displacement and rotation of rock mass and the abrupt release of massive energy once instability induces the failure (e.g., in situation of rockburst).